2013
DOI: 10.1175/mwr-d-12-00115.1
|View full text |Cite
|
Sign up to set email alerts
|

A New Parametric Tropical Cyclone Tangential Wind Profile Model

Abstract: A new parametric tropical cyclone (TC) wind profile model is presented for depicting representative surface pressure profiles corresponding to multiple-maxima wind profiles that exhibit single-, dual-, and triplemaximum concentric-eyewall wind peaks associated with the primary (inner), secondary (first outer), and tertiary (second outer) complete rings of enhanced radar reflectivity. One profile employs five key parameters: tangential velocity maximum, radius of the maximum, and three different shape velocity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…The SFMR radar can potentially provide along-track mapping of wind speeds at relatively high temporal (1 Hz) and spatial (~120 m) resolutions. The root-mean-square errors of the SFMR winds are less than 4 m/s~5 m/s [17,20], with validations of the measurements from dropwindsonde and an in situ instrument. …”
Section: Data Setsmentioning
confidence: 75%
See 1 more Smart Citation
“…The SFMR radar can potentially provide along-track mapping of wind speeds at relatively high temporal (1 Hz) and spatial (~120 m) resolutions. The root-mean-square errors of the SFMR winds are less than 4 m/s~5 m/s [17,20], with validations of the measurements from dropwindsonde and an in situ instrument. …”
Section: Data Setsmentioning
confidence: 75%
“…The modified SHEW model for a double-eye structure is based on the one-dimensional modified Rankine vortex functions [3,4,17] and double circles for the eyewalls containing maximum wind speeds. We organize the remainder of this paper as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Many parametric typhoon models have been developed to provide meteorological information for storm surge or storm wave modeling [41][42][43][44][45][46]. Since the authors of [47] found that the analytical models provided very similar results, the parametric typhoon model proposed in [43] was employed:…”
Section: Model Forcingmentioning
confidence: 99%
“…A common way to generate wind and air pressure fields for typhoons is to reconstruct them using the analytical parametric cyclone model. Over the years, many parametric cyclone models have been developed to provide meteorological information for storm surge modeling [43][44][45][46][47][48]. Jakobsen and Madsen [49] investigated and compared parametric cyclone models based on cyclone position, central pressure, maximum wind speed and radius to maximum wind speed.…”
Section: Parametric Cyclone Modelmentioning
confidence: 99%